Thermal management and non-reciprocal control of phonon flow via optomechanics - Alireza Seif (Nature Portfolio, 2018)
Phonon transport control is important for thermal and non-reciprocal devices. Here, Seif et al. combine heat transport in nanostructures and optomechanics into a platform for manipulating phonons with which they design an acoustic isolator and a thermal diode.